2014
DOI: 10.1016/j.neo.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

SC-2001 Overcomes STAT3-mediated Sorafenib Resistance through RFX-1/SHP-1 Activation in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma is the fifth most common solid cancer worldwide. Sorafenib, a small multikinase inhibitor, is the only approved therapy for advanced HCC. The clinical benefit of sorafenib is offset by the acquisition of sorafenib resistance. Understanding of the molecular mechanism of STAT3 overexpression in sorafenib resistance is critical if the clinical benefits of this drug are to be improved. In this study, we explored our hypothesis that loss of RFX-1/SHP-1 and further increase of p-STAT3 as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…Early mechanism dissection suggested that Sorafenib might function through inhibiting Raf‐1 and B‐Raf and the receptor tyrosine kinase activity of VEGFRs 1, 2 and 3 and PDGFR‐β . However, recent reports indicated that STAT3 activation also played a key role in the development of Sorafenib resistance in HCC cell lines . Our clinical studies using human HCC samples also demonstrated that higher expression of activated p‐STAT3 might indicate worse recurrence free survival under Sorafenib treatment.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Early mechanism dissection suggested that Sorafenib might function through inhibiting Raf‐1 and B‐Raf and the receptor tyrosine kinase activity of VEGFRs 1, 2 and 3 and PDGFR‐β . However, recent reports indicated that STAT3 activation also played a key role in the development of Sorafenib resistance in HCC cell lines . Our clinical studies using human HCC samples also demonstrated that higher expression of activated p‐STAT3 might indicate worse recurrence free survival under Sorafenib treatment.…”
Section: Discussionmentioning
confidence: 57%
“…To dissect the potential molecular mechanism(s) how ASC‐J9 ® combined with Sorafenib suppressed HCC cell invasion and proliferation, we first focused on p‐STAT3 signals as early studies indicated that Sorafenib resistance in HCC might be linked to altered p‐STAT3 signals . Interestingly, Lin et al .…”
Section: Resultsmentioning
confidence: 99%
“…The novel small molecule SC-2001 was shown to inhibit the transcriptional activities of STAT3 by enhancing SH-1 activity in hepatocellular carcinoma (HCC) cells [108]. This molecule has also been studied in combination with sorafenib, a multikinase inhibitor approved for treatment of unresectable HCC, advanced RCC, and thyroid cancer, where it was shown to overcome sorafenib resistance through the SH-1 pathway in HCC cell lines [109]. …”
Section: Blocking Stat3 Dimerization: Sh2 Domain Inhibitionmentioning
confidence: 99%
“…Several drug-treated 'oncogeneaddicted' cancer cells induce a positive feedback loop leading to STAT3 activation, consequently promoting cell survival and limiting overall drug response. For example, overactivation of STAT3 is associated with resistance to chemotherapy (i.e., taxol [137]) and targeted agents used in a variety of tumors, including the anti-EGFR mAb cetuximab, the anti-HER2/neu receptor mAb trastuzumab and TKIs erlotinib, sunitinib, sorafenib, crizotinib and imatinib mesylate [138][139][140][141]. The combined use of these agents with STAT3 inhibitors should be investigated in clinical trials, even to understand if STAT3 inhibitors should be administered from the start of targeted therapy to reduce primary resistance or at time of acquired resistance.…”
Section: Expert Opinionmentioning
confidence: 99%